General Election System In Indonesia Based On Law Of The Republic Of Indonesia NO. 7 OF 2017 - Siti Sarah; Sri Suatmiati (CV. Green Publisher Indonesia, 2022)
Each country claims that the system of government administration or the political system they build is a democracy. Indonesia is a country that bases its sovereignty on the people's sovereignty in addition to the basis of the rule of law to organize a democratic government by carrying out general elections using a separate system in legislative elections (DPR, DPD, Provincial DPRD, and Regency/City DPRD). The electoral system in Indonesia is inseparable from the recruitment function in the political system. The problem raised in this research is how is the general election system in Indonesia based on Law Number 7 of 2017 concerning General Elections, and what are the weaknesses of the open proportional system used in public elections in Indonesia? This research belongs to the normative legal research group prioritizes secondary data (library data and legislation). The nature of this research uses a descriptive-analytical method that describes the actual situation. The result of the study is that the general election system in Indonesia uses an Open Proportional System for the election of members of the Legislative Assembly (DPR, Provincial DPRD, and Regency/City DPRD) as stipulated in Article 168 paragraph (2) of Law Number 7 of 2017 concerning General Elections, while in section (3) specifies that the election to elect members of the DPD shall be carried out with a district system with many representatives. The disadvantages of using an open proportional system include that it is difficult for parties to integrate or cooperate by taking advantage of existing equations; this system facilitates party fragmentation; when a conflict arises within the party, it will be easy to break up, which often gives birth to new parties; this system gives the party leader an extreme position; the elected representatives may be separated from their constituents due to not knowing each other; and because of the large number of competing parties, it is difficult for a party to gain the majority in parliament needed to form a strong government.